The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.jpowsour.2017.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Energy management strategy for fuel cell-supercapacitor hybrid vehicles based on prediction of energy demand

Abstract: Offering high efficiency and producing zero emissions Fuel Cells (FCs) represent an excellent alternative to internal combustion engines for powering vehicles to alleviate the growing pollution in urban environments. Due to inherent limitations of FCs which lead to slow transient response, FC-based vehicles incorporate an energy storage system to cover the fast power variations. This paper considers a FC/supercapacitor platform that configures a hard constrained powertrain providing an adverse scenario for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 26 publications
0
53
0
Order By: Relevance
“…A picture of the laboratory station is shown in Figure 7. This station has already been used successfully to validate an EMS applied to hybrid vehicle in [30].…”
Section: Laboratory Station Descriptionmentioning
confidence: 99%
“…A picture of the laboratory station is shown in Figure 7. This station has already been used successfully to validate an EMS applied to hybrid vehicle in [30].…”
Section: Laboratory Station Descriptionmentioning
confidence: 99%
“…Of the available configurations it was found that connecting the FC and SC via DC/DC converters provides the best solution in terms of reducing the Vehicles 2020, 2, 1-17; doi:10.3390/vehicles2010001 www.mdpi.com/journal/vehicles Vehicles 2020, 2 2 stress on the fuel cell and achieving a high hydrogen economy because of the optimal fuel cell operation. A number of examples of this configuration have been presented in the literature, such as [16][17][18][19][20][21][22][23][24]. A control strategy based on reducing the transient changes on the FC load has been developed and experimentally tested in [16].…”
Section: Introductionmentioning
confidence: 99%
“…This was tested against the ECE15 EU drive cycle and performed acceptably. An energy management strategy utilising short-term future energy demand prediction was developed and tested through both simulation and experimentation in [18]. It was found that this strategy offers improved performance, owing partly to the better management of the SC for regenerative braking.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several energy management strategies (EMSs), namely rule‐based, optimization‐based and intelligent‐based, have been proposed for the mentioned hybrid structures in literature . Some examples of very recent proposed online EMSs can be found in . In , an online EMS based on data fusion approach is suggested.…”
Section: Introductionmentioning
confidence: 99%
“…The rule‐based of this work is based on a static PEMFC map. In , an EMS based on short‐term energy estimation is developed to maintain the SC state of energy within a defined limit. The PEMFC limits are based on a quasistatic model, and determining the power rate limits to avoid premature ageing is pointed out as a remaining issue.…”
Section: Introductionmentioning
confidence: 99%